2021
DOI: 10.31235/osf.io/kjcwh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Social Contagion of Blood Donations: Sustaining Repeated Prosocial Behaviour

Abstract: Repeated prosocial behaviour – behaviour that benefits unknown others and is individually costly – is crucial for the supply of many public goods. Experimental studies show that social mechanisms are pivotal for sustaining prosocial behaviour over time. One such mechanism is social contagion, which we broadly define as an individual changing their behaviour in response to the behaviour of others. This study examines to what extent and through what individual-level mechanisms social contagion affects repeated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…One strategy to achieve that may be group-donation programmes [ 60 ], where donors form groups that they can communicate and donate with–a promising area for future research. Such groups should create some actual feeling of relatedness, as previous studies have shown that social influence is at work among closely related individuals [ 17 , 61 , 62 ], but not among distant peers [ 63 ]. Finally, promoting communication about donations might be particularly effective for donors in early stages of their donor career, since their behaviour is more malleable than that of very experienced donors.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy to achieve that may be group-donation programmes [ 60 ], where donors form groups that they can communicate and donate with–a promising area for future research. Such groups should create some actual feeling of relatedness, as previous studies have shown that social influence is at work among closely related individuals [ 17 , 61 , 62 ], but not among distant peers [ 63 ]. Finally, promoting communication about donations might be particularly effective for donors in early stages of their donor career, since their behaviour is more malleable than that of very experienced donors.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy to achieve that may be group-donation programmes (Sun et al, 2019), where donors form groups that they can communicate and donate with. Such groups should create some actual feeling of relatedness, as previous studies have shown that social influence is at work among closely related individuals (Bruhin et al, 2020;Meyer & Tripodi, 2021;Schröder et al, 2021), but not among distant peers (Goette & Tripodi, 2022). Finally, promoting communication about donations might be particularly effective for donors in early stages of their donor career, since their behaviour is more malleable than that of very experienced donors.…”
Section: Discussionmentioning
confidence: 99%
“…Blood-donor identity of the parent. Based on the DIS-I questionnaire, Schröder et al (2021) constructed blood donor identity by considering the answers to the following questions evaluated on a 5-point Likert scale, where 1 signifies "completely disagree" and 5 "completely agree": "Being a blood/plasma donor is an important part of who I am." "Being a blood donor means more to me than just giving blood."…”
Section: Methodsmentioning
confidence: 99%
“…Thus, by supporting the transfer of the blood-donor behaviour from one generation of donors to another, blood banks may be able to ensure the long-term stability of the blood supply. This approach may be most relevant for blood banks whose strategy focuses on maintaining the loyalty of the existent donors rather than recruiting new donors as children can replace their parents in the donor pool and being a member of a donor network (family) is positively associated with blood donation (Schröder et. al., 2021).…”
Section: Limitations and Implicationsmentioning
confidence: 99%